2012
DOI: 10.1186/1471-2407-12-619
|View full text |Cite
|
Sign up to set email alerts
|

Survivin selective inhibitor YM155 induce apoptosis in SK-NEP-1 Wilms tumor cells

Abstract: BackgroundSurvivin, a member of the family of inhibitor of apoptosis proteins, functions as a key regulator of mitosis and programmed cell death. YM155, a novel molecular targeted agent, suppresses survivin, which is overexpressed in many tumor types. The aim of this study was to determine the antitumor activity of YM155 in SK-NEP-1 cells.MethodsSK-NEP-1 cell growth in vitro and in vivo was assessed by MTT and nude mice experiments. Annexin V/propidium iodide staining followed by flow cytometric analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 44 publications
5
49
0
Order By: Relevance
“…The results demonstrated that silencing of survivin expression, via specific inhibitor YM155, induced HCC cell apoptosis and growth arrest. These results corroborated those of previous studies regarding other neoplasms (8)(9)(10)(11)13,16). In order to represent a potential therapeutic strategy for HCC, the impacts of survivin, as well as YM155, on HCC should be sufficiently understood and validated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results demonstrated that silencing of survivin expression, via specific inhibitor YM155, induced HCC cell apoptosis and growth arrest. These results corroborated those of previous studies regarding other neoplasms (8)(9)(10)(11)13,16). In order to represent a potential therapeutic strategy for HCC, the impacts of survivin, as well as YM155, on HCC should be sufficiently understood and validated.…”
Section: Discussionsupporting
confidence: 79%
“…To date, this novel, small, imidazolium-based chemical has exhibited broad antitumor effects on various tumors, including Wilm's tumor, glioblastoma and breast cancer (6)(7)(8)(9). In addition, ongoing studies have demonstrated that YM155 may also enhance the chemosensitivity of cells to existing anticancer agents (4,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…YM155 was identified in a high-throughput screen to identify agents that selectively block survivin promoter activity and is the most clinically advanced of this new class of agents (40). It has demonstrated activity against various tumor types in preclinical studies (19,(40)(41)(42)(43). We selected the VHL null 786-O and the VHL wild-type Caki-1 cell lines as models for our xenograft studies as they both displayed high basal survivin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TNFα and TNFR1 by a pharmacological inhibitor and genetic silencing, respectively, reduced SMAC mimetic/ IFNα-triggered apoptosis. Tao et al suggested that survivin, an inhibitor of apoptosis, inhibitor induced programmed cell death in Wilms tumor cells by increasing expression of TNFR1 signaling [126].…”
Section: Tnf and Tnf Receptor 1-2 (Tnfr1 And Tnfr2)mentioning
confidence: 99%